The girl from the other side : Siúil, a Rún. Vol. 7 - Nagabe; MacFarlane, Ysabet Reinhardt (Seven Seas Entertainment, 2019)
Hounded by two transformed soldiers desperate for salvation and with Teacher reeling from revelations about his own forgotten former life, the past finally catches up to Teacher and Shiva. With danger closing in around them at terrifying speed, is there nowhere safe for them to live a normal life together<U+2026>?